Effect of early maternal newborn skin to skin contact in labour room on third stage of labour and success at breastfeeding - Parikh, Purvi M.; Agrawal, Saumya P.; Vyas, Rupa C.; Shah, Sapana R.; Joshi, Khushi P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Immediate postpartum period and birth pose many challenges for the mother and the new-born. Initiation of early skin to skin contact in the labour room can be beneficial to both of them. Methods: Randomized control trial conducted over a period of 7 months in a tertiary care centre enrolling 400 laboring women.200 in the control group were given routine care. In the 200women in the study group, the newborn was given immediate skin to skin contact by placing him/her on the mother’s chest. Results: Duration of third stage of labour was less than 10 minutes in 95%women of study group compared to 56% women in the control group(p<0.01). Placenta was expulsed as a whole in 98% cases in the study group compared to 81% in the control group. Successful breastfeeding was observed in 88% women in study group compared to 54%in the control group(p<0.01). Breastfeeding was initiated within 30 minutes of birth in 96%women in the study group compared to 41% in the control group. Conclusions: Uterus could contract faster with the complete expulsion of placenta and shortening of the third stage of labour with early skin to skin contact. The newborn showed early initiation, success at breastfeeding and longer first breastfeeding with early skin to skin contact.